Pangenomic Identification of Metabolic Switches in Kosakonia cowanii: A Consolidated Network Biology Approach - Campos, Davi Mota; Fonseca, Gustavo Henrique Leal da; Cândido, Arthur Rodrigues; Tebaldi, Nilvanira Donizete; Mota, Lara Caroline Borges Moreira; Corrêa, Joberth Lee; Santos, Ana Carolina Costa; Vieira, Carlos Ueira; Santos, Anderson Rodrigues dos (Anais da Escola Regional de Informática do Triângulo Mineiro (ERI-TM), 2026)
Kosakonia cowanii acts as both a plant growth-promoting rhizobacterium (PGPR) and an opportunistic pathogen. To characterize this lifestyle transition, we built a pangenomic pipeline across 77 genomes, consolidating strain-specific interactomes into a species-level graph. Biological coherence filters discarded 12,000 false-positive orthology mappings. Applying Bridging Centrality (BriCe) with functional bridging criteria identified 46 conserved metabolic switches at the PGPR-pathogen interface. These switches, including flagellar regulators and MFS transporters, are tractable targets for experimental validation.